Optimal sizing of hybrid tidal, photovoltaic and battery sources of energy - Sadeghi, Omid Sarrafan (2015)
A methodology for calculating the optimum size of the hybrid tidal, photovoltaic and battery by considering the uncertainty of renewable sources is proposed. In the method the uncertainty is investigated using the water velocity and sun irradiation probability functions. The numbers of solar arrays, tidal turbines and battery were considered as optimization variables which have been determined by the particle swarm optimization algorithm. In the sizing problem, cost is proposed as the objective function of the algorithm, which is calculated by the Net Present Cost method. The cost function includes capital, replacement, and operation and maintenance costs for each unit of renewable source for a hybrid with 20 years life time. One of the constraints that is considered in the sizing problem is, maintaining the reliability in a specific value. The Equivalent Loss Factor index is considered as reliability index which should be in the range [0, 0.1] as ideal reliability for the system. In the proposed method sequential Monte Carlo method is used to consider the uncertainty in renewable sources. In order to compare the previous methods and proposed method, cost and reliability indices are regarded as comparison factors. The cost that is calculated in the sizing problem with the hourly data of sun radiation and water velocity is considered as the reference of comparison. In addition the reliability factor that is proposed with the Monte Carlo method is regarded as the ideal reliability index. Moreover, the sizing problem is also investigated without considering the uncertainty with the average data of sun irradiation and water velocity. The results of simulation with average data reveals that the total cost is 21% less than the cost which uncertainty is taken into account in renewable sources with Monte Carlo method, however the reliability index for the simulation with the average data calculated with the Monte Carlo method, shows that the system reliability in this case is, 177% less than ideal reliability index. In fact, using the average data of water velocity and solar irradiation leads to lower cost, but it gives wrong design for the system as it cannot supply the load completely. Therefore considering the uncertainty in renewable sources give more realistic view to the sizing problem.